2010
DOI: 10.1097/pap.0b013e3181f89400
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Immunohistochemistry in the Diagnosis of Metastatic Clear Cell Renal Cell Carcinoma

Abstract: The diagnosis of metastatic clear cell renal cell carcinoma may be difficult in some cases, particularly in the small image-guided biopsies that are becoming more common. As targeted therapies for renal cell carcinoma are now standard treatment, the recognition and diagnosis of renal cell carcinoma has become even more critical. Many adjunctive immunohistochemical markers of renal epithelial lineage such as CD10 and RCCma have been proposed as aids in the diagnosis of metastatic renal cell carcinoma, but low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 178 publications
(169 reference statements)
1
40
0
1
Order By: Relevance
“…Other studies have shown that PAX8 is more sensitive (88-100%) for metastatic RCCs than other commonly used markers, such as CD10 (59-82%), EMA (67-77%) and RCC marker (72-95%) [8]. Sangoi et al [6] proposed replacing CD10 and RCC markers with PAX2 and PAX8 as markers in the workup for potential metastatic renal tumors, and Ozcan et al [7] supported this by suggesting that PAX2 and PAX8 are the best markers for metastatic RCCs. An additional use for PAX8 is that, since PAX8 is expressed in thyroid follicular cells, it will be positive in cytologic specimens of metastatic thyroid malignancies [1,12,22,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown that PAX8 is more sensitive (88-100%) for metastatic RCCs than other commonly used markers, such as CD10 (59-82%), EMA (67-77%) and RCC marker (72-95%) [8]. Sangoi et al [6] proposed replacing CD10 and RCC markers with PAX2 and PAX8 as markers in the workup for potential metastatic renal tumors, and Ozcan et al [7] supported this by suggesting that PAX2 and PAX8 are the best markers for metastatic RCCs. An additional use for PAX8 is that, since PAX8 is expressed in thyroid follicular cells, it will be positive in cytologic specimens of metastatic thyroid malignancies [1,12,22,28].…”
Section: Discussionmentioning
confidence: 99%
“…In müllerian tract malignancies, WT-1, ER, PR, and CA125 stain positive, although these markers are limited in their specificity [4,5]. For metastatic RCC, immunohistochemical stains such as the RCC marker and CD10 have been used; however, markers with a better sensitivity and specificity are also needed [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2e), and PAX8 is a transcription factor that is sensitive and specific for RCC (Fig. 2f) [6]. Based on the immunohistochemistry with positive CD10, PAX8, AE1/AE3, and negative GATA-3, the diagnosis of metastatic RCC was made.…”
Section: Case Reportmentioning
confidence: 99%
“…2a–f). CK 5/6 and p63 are markers for squamous cell carcinoma, SOX-10 and pan-melanocytic cocktail are markers for melanoma, and adipophilin is positive in sebaceous lesions but can also be a sensitive marker for RCC [5, 6]. CD10 is a metallomembrane endopeptidase that is highly sensitive but not specific for RCC (Fig.…”
Section: Case Reportmentioning
confidence: 99%